Constitutional guarantees of the inviolability of property rights on the example of Ukraine, Poland and Germany - Hanna Nechyporuk; Liudmyla Mikhnevych; Yevheniia Bondarenko; Iryna Yermolenko (Universidad Hemisferios, 2023)
In the course of the modern state building processes, European integration of Ukraine, as well as negative events unfolding as a result of Russia's armed aggression, the property right as one of the fundamental constitutional rights is experiencing restrictions and transformations. The purpose of the scientific research is to highlight the content of the guarantee (principle) of the inviolability of property rights, and how they are embedded in the Fundamental Laws of Ukraine, Poland and Germany. The following general and specifically legal methods of scientific knowledge form the methodological basis of the study: the system-structural method, the method of comparison and logical-legal method. The analysis of constitutional guarantees regarding the inviolability of property rights on the example of Ukraine, Poland and Germany was conducted in the article. According to the results of the conducted research, it is proposed the following separation of the guarantees regarding the inviolability of property rights stipulated by the constitutions guarantees of legislative consolidation of rights and procedures; immediate principles and guarantees of effectuation of the property rights; guarantees of administrative support; guarantees of protection and defense of the property rights. Significance of results and the prospects for further research. The proposed classification makes it possible to more widely define the constitutional guarantees of the property rights, which also makes it possible to provide the legal protection to a wider range of public relations regarding the property.